PERAN PLATFORM DIGITAL DALAM PENINGKATAN PARTISIPASI PETANI PADI SAWAH DI DESA BOU KECAMATAN LAMBANDIA KABUPATEN KOLAKA TIMUR - Putri, Widya Febiola Andriani; Rela, Iskandar Zainuddin; Lasinta, Megafirmawanti (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
Fluctuations and declines in rice production, particularly in East Kolaka Regency, reflect structural problems in the production system related to farmers' limited access to information and technology. Therefore, the use of digital platforms has the potential to become a strategic instrument for increasing the participation of rice farmers, especially at the village level, such as in Bou Village. The purpose of this study is to analyze the role of digital platforms in increasing the participation of rice farmers in Bou Village, Lambandia District, East Kolaka Regency. This study uses a descriptive qualitative approach. Research informants were determined using purposive sampling techniques with specific criteria. There were 13 informants. Data collection was carried out in a natural setting by applying observation techniques, in-depth interviews, documentation, and literature studies. This study focused on three main aspects, namely the types of digital platforms used by farmers, the role of digital platforms, and the level of participation of rice farmers. Data analysis was performed using qualitative descriptive analysis. The results of the study indicate that digital platforms play a strategic role in increasing the participation of rice farmers in Bou Village, Lambandia District, East Kolaka Regency. Facebook, YouTube, and WhatsApp form a complementary digital learning and communication ecosystem, enabling farmers to be more actively involved in the planning, implementation, and evaluation of farming activities. These platforms not only serve as sources of information but also strengthen social interaction, non-formal learning, and the sustainability of agricultural practices through intensive and responsive communication. The integration of information, relationships, and sustainability functions encourages a shift in farmers' participation patterns from passive to participatory and collaborative based on digital technology. This study on agricultural development communication emphasizes the importance of cross-platform integration in shaping farmer participation. Additionally, it highlights the need for contextual, adaptive, and farmer-needs-oriented extension strategies and agricultural digitization policies at the local level.